Modulation of synaptic transmission through O-GlcNAcylation - Seunghyo Han; Jun-Nyeong Kim; Chan Ho Park; Jin-Seok Byun; Do-Yeon Kim; Hyoung-Gon Ko (Molecular Brain, 2024)
Abstract O-GlcNAcylation is a posttranslational modification where N-acetylglucosamine (O-GlcNAc) is attached and detached from a serine/threonine position by two enzymes: O-GlcNAc transferase and O-GlcNAcase. In addition to roles in diabetes and cancer, recent pharmacological and genetic studies have revealed that O-GlcNAcylation is involved in neuronal function, specifically synaptic transmission. Global alteration of the O-GlcNAc level does not affect basal synaptic transmission while the effect on synaptic plasticity is unclear. Although synaptic proteins that are O-GlcNAcylated are gradually being discovered, the mechanism of how O-GlcNAcylated synaptic protein modulate synaptic transmission has only been reported on CREB, synapsin, and GluA2 subunit of AMPAR. Future research enabling the manipulation of O-GlcNAcylation in individual synaptic proteins should reveal hidden aspects of O-GlcNAcylated synaptic proteins as modulators of synaptic transmission.